Solutions of Islamic Lesson Learning in Interest Problem by Using Variety of Teaching Style - Sri Herlina (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2021)
This study is based on indications that the level of interest in learning students towards Islamic Religious Education (PAI) subjects is still low before getting action. Then after it is known that the low interest in learning, then researchers offer solutions with the concept of Teaching Style Variations. Researchers use Class Action Research (PTK) with quantitative approach. As for the data collection techniques in this study, researchers used three techniques, namely observation, questionnaire and docume ntation. Observations used by researchers are observation sheets related to Variations in Teaching Style. Based on the results of the data analysis, it can be concluded that, The Interest of Learning Grade II Students in Islamic Religious Education Subjects (PAI) before getting action (Through Variations in Teaching Style) is still low, which is 29.75%. But once they get a Variety of Teaching Styles or actions in the first cycle the student's interest level gets better, even the change in the student's increases cyclically, which is 60.25%. Or their interest increase by 30.5%. This shows that with the implementation of Teaching Style Variations are useful to increase the interest in learning.